The effect of motor cortex stimulation in deafferentated rats - Rusina, Robert; Vaculín, Šimon; Yamamotová, Anna; Barek, Stephan; Dvořáková, Helena; Rokyta, Richard (Neuro-endocrinology letters, 2005)
OBJECTIVES: The aim of the study was to describe the effect of motor cortex stimulation (MCS) on pain thresholds in deafferentated rats. SETTINGS AND DESIGN: The effect of MCS was studied in 18 deafferentated and 14 intact laboratory rats, using a standardised plantar test and tail-flick latencies. Two inoxious stimulation electrodes were implanted subdurally over the cerebral cortex and a C5-Th1 dorsal root rhizotomy was performed on the left side. Pain thresholds were measured before and after cortical stimulation. The data were analysed with ANOVA for repeated measures. RESULTS: MCS in intact animals evoked no changes in pain thresholds except for the contralateral forelimb, in which the pain threshold increased after MCS. Following deafferentation, pain thresholds increased in both plantar test and tail-flick in comparison to baseline values. When MCS was applied to the deafferentated animals, the pain thresholds returned to baseline levels. The effect of MCS disappeared within 24 hours. MAIN FINDINGS: 1. MCS in intact animals evoked hypoesthesia in the corresponding contralateral forelimb; 2. deafferentation itself increased pain thresholds in the unaffected limbs; 3. under MCS, pain thresholds in deafferentated rats were not different from pre-dafferentation values; 4. the effect of MCS disappeared in 24 hours and oscillated. CONCLUSIONS: Our results show a similar effect of the stimulation in man and experimental animals despite the differences in the organisation of the cerebral cortex. The use of laboratory animals is promising for further studies in the field of involved antalgic mechanisms of MCS.
Keywords: Nociceptors; financování organizované; práh bolesti; Rhizotomy; Rats; Denervation; denervace; motorické korové centrum; potkani Long-Evans; mužské pohlaví; nociceptory; krysa rodu Rattus; Motor Cortex; Financing, Organized; ženské pohlaví; rizotomie; zvířata; Rats, Long-Evans; elektrická stimulace; Pain Threshold; Causalgia; Female; Electric Stimulation; kauzalgie; Male; Animals